MATLAB Answers

MuPAD error

1 view (last 30 days)
Alex
Alex on 4 Apr 2012
Hey all,
I've been debugging this code for a while now, but I can't for the life of my find out what's wrong with this. Whenever I run into a MuPAD error, Mybest solution is usually to come here, so I'm here again? Can someone look through this code and help me out a bit? More eyes are always better, and I'd love to learn more about fixing MuPAD errors. Here's the code:
data = csvread('data.csv');
assert (mod(size(data, 1), 1) == 0, ...
'Input data must have an integer multiple of 1 rows');
assert (size(data, 2) == 8, ...
'Input data must have exactly eight columns.');
syms d1;
nsys = size(data, 1);
for k = 1 : nsys,
F = solve_d_two_layers_eq(data((k-1) + (1:1), 1:end));
d(k, :) = solve(F);
end
dd = double(d);
fid=fopen('d_values.csv','w');
fprintf(fid,'%+5.5f, %+5.5fi\n',[real(dd(:)), imag(dd(:))].');
fclose(fid);
And the function file:
function F = solve_d_two_layers_eq(p)
assert (ndims(p) ==2, ...
'System parameters ''p'' must be 2D matrix.');
assert (all(size(p) ==[1,8]), ...
'System parameters must be 1-by-8 matrix.');
syms d1
n0 = 1;
y = p(:,1);
R = p(:,2);
n1 = p(:,3);
k1 = p(:,4);
n2 = p(:,5);
k2 = p(:,6);
n3 = p(:,7);
k3 = p(:,8);
d2 = 300;
g1 = (n0.^2 - n1.^2 - k1.^2)./((n1 + n2).^2 + k1.^2);
g2 = (n1.^2 - n2.^2 + k1.^2 - k2.^2)./((n1 + n2).^2 + (k1 + k2).^2);
h1 = (2.*n0.*k1)./((n0 + n1).^2 + k1.^2);
h2 = (2.*(n1.*k2 - n2.*k1))./((n1 + n2).^2 + (k1 + k2).^2);
a1 = (2.*pi().*k1.*d1)./y;
b1 = (2.*pi().*n1.*d1)./y;
p2 = (exp(a1)).*cos(b1);
q2 = (exp(a1)).*sin(b1);
t2 = (exp(-1.*a1)).*(g2.*(cos(b1)) + h2.*(sin(b1)));
u2 = (exp(-1.*a1)).*(h2.*(cos(b1)) - g2.*(sin(b1)));
p12 = p2 + g1.*t2 - h1.*u2;
q12 = q2 + h1.*t2 + g1.*u2;
t12 = t2 + g1.*p2 - h1.*q2;
u12 = u2 + h1.*p2 + g1.*q2;
g3 = (n2.^2 - n3.^2 + k2.^2 - k3.^2)./((n2 + n3).^2 + (k2 + k3).^2);
h3 = (2.*(n2.*k3 - n3.*k2))./((n2 + n3).^2 + (k2 + k3).^2);
a2 = (2.*pi().*k2.*d2)./y;
b2 = (2.*pi().*n2.*d2)./y;
p3 = (exp(a2)).*(cos(b2));
q3 = (exp(a2)).*(sin(b2));
t3 = (exp(-1.*a2)).*(g3.*(cos(b2)) + h3.*(sin(b2)));
u3 = (exp(-1.*a2)).*(h3.*(cos(b2)) - g3.*(sin(b2)));
r2 = (exp(a1)).*(g2.*(cos(b1)) - h2.*(sin(b1)));
s2 = (exp(a1)).*(h2.*(cos(b1)) + g2.*(sin(b1)));
v2 = (exp(-1.*a1)).*(cos(b1));
w2 = (-1.*(exp(-1.*a1))).*(sin(b1));
r12 = r2 + g1.*v2 - h1.*w2;
s12 = s2 + h1.*v2 + g1.*w2;
v12 = v2 + g1.*r2 - h1.*s2;
w12 = w2 + h1.*r2 + g1.*s2;
p13 = p12.*p3 - q12.*q3 + r12.*t3 - s12.*u3;
q13 = q12.*p3 + p12.*q3 + s12.*t3 + r12.*u3;
t13 = t12.*p3 - u12.*q3 + v12.*t3 - w12.*u3;
u13 = u12.*p3 + t12.*q3 + w12.*t3 + v12.*u3;
F = (t13.^2 + u13.^2)./(p13.^2 + q13.^2) - R;
  1 Comment
Alexander
Alexander on 5 Apr 2012
What error message do you get?

Sign in to comment.

Answers (0)

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!